ANALISIS LAPORAN KEUANGAN SEBELUM DAN SELAMA PANDEMI COVID-19 TERHADAP KINERJA KEUANGAN PERUSAHAAN - Cholipah Hayuningtiya; Ali Muhajir (Pro-fit, 2023)
This study aims to find out how the company’s financial performance at PT Industri Jamu dan Farmasi Sido Muncul Tbk with analizing financial statements before and during the covid-19 pandemic. This study used secondary data and documentation method, for sampling used purposive sampling method and used quantitative descriptive for data analysis method. The results of this study indicate that there are differences in financial performance at PT Industri Jamu and Farmasi Sido Muncul Tbk before and during the COVID-19 pandemic. Calculations used financial ratios show that covid-19 does not have a negative impact on financial performance at PT Industri Jamu dan Farmasi Sido Muncul Tbk, this is because when COVID-19 occurs, the calculation results show an increase percentage almost all in financial ratios except for the liquidity ratio, but the level of efficiency of the company's financial performance can still be said to be good, this is because even though there is a decrease in the liquidity ratio, the calculation results can still meet existing industry standards.